1992
DOI: 10.1096/fasebj.6.9.1319362
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of voltage‐gated Ca 2+ entry into GH 3 and chromaffin cells by imidazole antimycotics and other cytochrome P450 blockers

Abstract: We have studied the effects of cytochrome P450 inhibitors on the entry of Ca2+ and Mn2+, used here as a Ca2+ surrogate for Ca2+ channels, in fura-2-loaded GH3 pituitary cells and bovine chromaffin cells depolarized with high-K+ solutions. Imidazole antimycotics were potent inhibitors (econazole greater than miconazole greater than clotrimazole greater than ketoconazole). alpha-Naphtoflavone and isosafrole, but not metyrapone, also inhibited the entry of Ca2+ and Mn2+ induced by depolarization. This inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 27 publications
(3 reference statements)
2
58
0
Order By: Relevance
“…These effect include inhibition of Ca 2ϩ entry via the dihydropyridine-sensitive Ca 2ϩ channels of the plasma membrane (35,36), inhibition of cell proliferation (37), and blockade of release of von Willebrand factor from cultured endothelial cells (38,39). Studies in a mouse model for ␤ thalassemia have indicated that combination of CLT with either recombinant human erythropoietin (r-HuEPO) or hydroxyurea induces a greater increase in Hb levels compared to therapy with r-HuEPO or hydroxyurea alone (40).…”
Section: Discussionmentioning
confidence: 99%
“…These effect include inhibition of Ca 2ϩ entry via the dihydropyridine-sensitive Ca 2ϩ channels of the plasma membrane (35,36), inhibition of cell proliferation (37), and blockade of release of von Willebrand factor from cultured endothelial cells (38,39). Studies in a mouse model for ␤ thalassemia have indicated that combination of CLT with either recombinant human erythropoietin (r-HuEPO) or hydroxyurea induces a greater increase in Hb levels compared to therapy with r-HuEPO or hydroxyurea alone (40).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when such channels are closed by nimodipine in the rat hepatic artery, the subsequent relaxations to EDHF and levcromakalim are reduced (Zygmunt 1994b). Since cytochrome P450 inhibitors, including clotrimazole and proadifen, are also inhibitors of voltage-sensitive Ca-channels (Kalsner et al, 1970;Triggle et al, 1979;Villalobos et al, 1992), this action may thus contribute to their effect on EDHF-mediated relaxations. Fulton et al (1994) showed that clotrimazole had no effect on the vasodilatation produced by bolus injections of cromakalim into rat coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…[Ca2+], measurements were performed as described previously (Villalobos, Fonteriz, Lopez, Garcia & Garcia-Sancho, 1992;Lopez, Garcia, Artalejo, Neher & Garcia-Sancho, 1995). Briefly, cell-coated coverslips loaded with fura-2 AM (the acetoxymethyl ester form of fura-2; Grynkiewicz, Poenie & Tsien, 1985) were placed under the inverted microscope (Nikon Diaphot, x40 oilimmersion objective lens) and fluorescence images were processed using an Applied Imaging MagiCal image processor (Sunderland, UK).…”
Section: Methodsmentioning
confidence: 99%